Volume, protein and calcium content of milk of some Filipino mothers - Bongga, Demetria C. 1941-; Hernadez, Teresita B. (1968)
Milk secretion especially among mothers in developing countries were shown to be poor in quality and quantity to sustain maximum growth of infants even during the first year of life. This study was made to determine the average volume as well as the protein and calcium contents of milk secretion of some Filipino mothers. Babies were weighed before and after feeding for one day and changes in weight were taken as the amount of milk secreted by the mother. Milk samples were collected after the test feeding and were analyzed for protein using the Nessler's Calorimeric method, and calcium using the CDTA titration method. Average 24-hour milk secretion of the mothers was 600 ml during the first semester and only 300 ml during the second semester of lactation. Calcium level in milk was 25mg/100ml, slightly lower than European average of 34mg/100ml. However, milk protein level was found to be comparable with that observed among mothers from well-fed populations. Milk secretion appeared to be less during the later months of lactation as compared with that during the first four months. Although protein and calcium concentration in milk remained relatively constant from month to month. With the small volume of milk secreted by the mothers it was evident that the infants in the study have not received sufficient calories, protein and calcium from the mothers.
Thesis (M.S. Foods and Nutrition)--University of the Philippines, Diliman.
Keywords: Milk, Human